2018
DOI: 10.1016/j.nicl.2018.08.006
|View full text |Cite
|
Sign up to set email alerts
|

FDG PET Parkinson’s disease-related pattern as a biomarker for clinical trials in early stage disease

Abstract: BackgroundThe development of therapeutic interventions for Parkinson disease (PD) is challenged by disease complexity and subjectivity of symptom evaluation. A Parkinson's Disease Related Pattern (PDRP) of glucose metabolism via fluorodeoxyglucose positron emission tomography (FDG-PET) has been reported to correlate with motor symptom scores and may aid the detection of disease-modifying therapeutic effects.ObjectivesWe sought to independently evaluate the potential utility of the PDRP as a biomarker for clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 42 publications
4
46
2
Order By: Relevance
“…Since the theory of parkinsonism-related patterns was proposed by Eidelberg (Eckert et al, 2005), 18 F-FDG PET has been developed specifically to identify and measure metabolic abnormalities in parkinsonism. Many research showed that FDG PET has a very good ability to differentiate PD, MSA, PSP, and CBD according to the glucose metabolism pattern (Eckert et al, 2005; Huang et al, 2007; Teune et al, 2013; Matthews et al, 2018). The prominent network abnormality detected in PD is characterized by increased pallidothalamic and pontine metabolic activity, associated with reductions in the premotor cortex and parietal associate regions.…”
Section: Discussionmentioning
confidence: 99%
“…Since the theory of parkinsonism-related patterns was proposed by Eidelberg (Eckert et al, 2005), 18 F-FDG PET has been developed specifically to identify and measure metabolic abnormalities in parkinsonism. Many research showed that FDG PET has a very good ability to differentiate PD, MSA, PSP, and CBD according to the glucose metabolism pattern (Eckert et al, 2005; Huang et al, 2007; Teune et al, 2013; Matthews et al, 2018). The prominent network abnormality detected in PD is characterized by increased pallidothalamic and pontine metabolic activity, associated with reductions in the premotor cortex and parietal associate regions.…”
Section: Discussionmentioning
confidence: 99%
“…In collaboration with Eidelberg et al, PDRPs were identified in independent American, Indian, Chinese, and Slovenian populations [11,15,20,21]. Independently from these authors, the PDRP was recently derived in an Israeli population [22]. These PDRPs were highly similar to the PDRP USA , although minor deviations in PDRP regional topography were observed in several of these studies, which may be caused by differences in demographics or clinical characteristics of the cohorts.…”
Section: Introductionmentioning
confidence: 93%
“…Despite the clinical heterogeneity of disease manifestations, metabolic activity assessed with 18 F-fluorodeoxyglucose ( 18 F-FDG) PET in conjunction with multivariate computing algorithms has revealed disease-specific brain network patterns in parkinsonism ( Ma et al, 2007 , Eckert et al, 2008 , Teune et al, 2013 , Matthews et al, 2018 ). It can reliably differentiate between various parkinsonian syndromes even during early stages ( Spetsieris et al, 2009 , Tang et al, 2010 , Tripathi et al, 2016 ) by measuring expression scores of multiple disease patterns prospectively in any new subjects.…”
Section: Introductionmentioning
confidence: 99%